First record of the basking shark Cetorhinus maximus (Lamniformes: Cetorhinidae) in Indonesia - Fahmi, F; White, WT (2015)
A recent stranding of a basking shark Cetorhinus maximus in north-western Bali represents the first confirmed record of this large, filter-feeding shark species in Indonesian waters. Based on measurements of the fins and claspers, the adult male specimen was estimated to be between 5.6 and 8.1 m LT, with an average estimate of 6.7 m LT. It is possible that the Indonesian Throughflow is an important route for this species during transequatorial migrations.